88.8k views
2 votes
What is the sum of zeros of the equation (m-10)(6m-1)=0. Ancwer your question as a fraction

PLSSS SOMEONE ANCWEE THISS BEGGINGG.​

User Kevinkt
by
4.9k points

1 Answer

2 votes

Answer:

The sum of zeros is
(61)/(6)

Explanation:

The Rule of Zero Product

The rule of zero product states that the product of two nonzero elements is nonzero. It can be written as the following assertion:

If a.b=0, then a=0 or b=0

The equation

(m-10)(6m-1)=0

can be solved by applying the mentioned rule:


m-10=0 \ \ \Rightarrow m=10


6m-1=0 \ \ \Rightarrow m=1/6

The sum of both solutions is:


\displaystyle 10+(1)/(6)=(61)/(6)

The sum of zeros is
\mathbf{(61)/(6)}

User Quentinadam
by
5.6k points